From face cellulitis to periorbital necrotizing fasciitis induced by Streptococcus pyogenese: a case report - Pellat Andréanne; Zwetyenga Narcisse; Brie Alice; Gengler Charline (Journal of Oral Medicine and Oral Surgery, 2024)
Groupe A Streptococcus (SGA) is one of the main bacteria involved in skin and soft tissue infections. Since September 2022, we observe a resurgence of cases of SGA infections associated with an increased mortality. Periorbital localization for necrotizing fasciitis is rare. The most common etiology is dental infection. This affection requires early treatment, associating antibiotherapy and surgery. We report here a case of dental cellulitis evolving in periorbital necrotizing fasciitis. This patient needed intensive care treatment and tracheotomy. Two surgical procedures were necessary for debridement. After the acute phase, two more surgical procedures were realized for eyelids reconstruction. The aim of this case report is alert to the possible evolution of dental cellulitis during a period of SGA's epidemic.